Treatment of moderate grade dog bite wounds using amoxicillin–clavulanic acid with and without enrofloxacin: a randomised non‐inferiority trial. Issue 9 (20th June 2021) - Kalnins, NJ; Haworth, M; Croton, C; Gibson, JS; Stewart, AJ; Purcell, SL
Abstract : Background: Dog‐to‐dog bite wounds are a common veterinary emergency presentation: despite this, there is insufficient information to guide veterinarians on appropriate empirical antimicrobial management. Objectives: Investigate the effectiveness of amoxicillin–clavulanic acid with and without enrofloxacin in the treatment of moderate grade dog bite wounds (DBW). To describe common pathogens and their antimicrobial susceptibility patterns. Materials and methods: In a single‐centre parallel group pragmatic trial, 50 dogs presenting with moderate grade DBW were prospectively randomised to receive amoxicillin–clavulanic acid (group A) or amoxicillin–clavulanic acid and enrofloxacin (group B). Swabs were taken for culture and susceptibility testing at admission. Stabilisation, wound care and surgical debridement were performed at the discretion of admitting clinicians. The primary outcome was complication due to infection at 10 days, with Bayesian inference used to estimate the difference in proportions between treatment groups. Results: Of the 24 dogs in treatment group A, 1 required the addition of enrofloxacin at re‐examination. None of the 26 dogs in group B required alteration of antimicrobial coverage. The difference in complication rate due to infection between treatment groups was 4.2%. Twenty‐one different organisms were identified: Staphylococcus pseudintermedius, Neisseria spp., Pasteurella multocida and P . canis were the most common. Over 90% of gram‐negative and gram‐positive isolates were susceptible to amoxicillin–clavulanic acid. Ninety‐six percent of gram‐negative and 86% of gram‐positive isolates were susceptible to enrofloxacin. Conclusion and clinical significance: Amoxicillin–clavulanic acid is an appropriate empirical antimicrobial choice for moderate DBW in South East Queensland. Reduced empirical enrofloxacin use will promote antimicrobial stewardship and potentially antimicrobial resistance.